Metabolic subtyping reveals PDIK1L as a dual-functional regulator of progression and PARP inhibitor sensitivity in prostate cancer - Wang, Zhongyuan; Ge, Qintao; Aihetaimujiang, Anwaier; Zhang, Ji; Lu, Jiahe; Yang, Jianfeng; Chen, Yonghao; Qin, Bin; Zhang, Hailiang; Xu, Wen-Hao; Ye, Dingwei (Frontiers in Cell and Developmental Biology, 2025)
BackgroundProstate cancer demonstrates significant metabolic heterogeneity, but its role in therapeutic resistance and disease progression remains unclear. This study investigates the clinical implications of metabolic diversity and identifies potential biomarkers for precision oncology.MethodsMulti-omics analyses of TCGA-PRAD and meta-cohorts classified tumors into three metabolic subtypes (C1, C2, C3). Functional studies utilized prostate cancer cell lines with genetic modulation of PDIK1L. Proliferation assays, protein expression analysis, and drug sensitivity evaluations were systematically performed.ResultsMetabolic subtyping delineated distinct molecular and clinical profiles. The C2 subtype demonstrated elevated genomic instability and heightened sensitivity to PARP inhibitors, characterized by enrichment of glycogen metabolism and TP53-driven oncogenic pathways. Integrative multi-omics and random survival forest analysis prioritized PDIK1L as a C2-specific biomarker, where its overexpression accelerated tumor proliferation and rewired metabolic programs to confer resistance to PARP inhibitors. Conversely, PDIK1L knockdown suppressed proliferation and sensitized cells to therapy, underscoring its role as a dual-functional regulator. Mechanistically, PDIK1L interacted with DNA repair and metabolic adaptation pathways, creating a permissive environment for therapeutic resistance. Combinatorial therapy with Enzalutamide and PARP inhibitors effectively reversed PDIK1L-mediated resistance, restoring drug sensitivity across preclinical models. Independent validation in multi-institutional cohorts confirmed the robustness of metabolic subtyping and PDIK1L’s prognostic value in predicting survival and treatment outcomes.DiscussionMetabolic stratification reveals the C2 subtype as a high-risk prostate cancer group with unique therapeutic vulnerabilities. PDIK1L emerges as a dual-functional biomarker driving tumor progression and modulating treatment efficacy, offering a novel target for precision therapeutic strategies.